2008
DOI: 10.1183/09031936.00086707
|View full text |Cite
|
Sign up to set email alerts
|

Sequential measurements of procalcitonin levels in diagnosing ventilator-associated pneumonia

Abstract: The utility of procalcitonin levels to improve the accuracy of clinical and microbiological parameters in diagnosing ventilator-associated pneumonia (VAP) was evaluated.Sequential measurement of procalcitonin and C-reactive protein levels and the calculation of the simplified Clinical Pulmonary Infection Scores (CPIS) were performed in 44 patients mechanically-ventilated for .48 h with neither active infection for the duration or suspicion of VAP. Patients who developed extrapulmonary infection were excluded.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 27 publications
3
59
1
4
Order By: Relevance
“…He found clinical pulmonary infection score ≥6 had 78% sensitivity and 80% specificity. A clinical pulmonary infection score ≥6 combined with serum procalcitonin levels ≥2.99 ng/ml resulted in 100% specificity [12]. According to the guideline of American Thoracic Society [1], there were 63 VAP cases in our study but only 43 VAP cases (68.25%) in the VAP group had serum procalcitonin level >0.5 ng/ml and 20 VAP cases (31.75%) in the VAP group had serum procalcitonin level ≤0.5 ng/ml (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…He found clinical pulmonary infection score ≥6 had 78% sensitivity and 80% specificity. A clinical pulmonary infection score ≥6 combined with serum procalcitonin levels ≥2.99 ng/ml resulted in 100% specificity [12]. According to the guideline of American Thoracic Society [1], there were 63 VAP cases in our study but only 43 VAP cases (68.25%) in the VAP group had serum procalcitonin level >0.5 ng/ml and 20 VAP cases (31.75%) in the VAP group had serum procalcitonin level ≤0.5 ng/ml (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] In the only study in which procalcitonin was found to be a good diagnostic marker for VAP, only 20 patients were included and those with a previous infection during the same hospitalization were excluded, limiting the potential value of this marker to a very limited subset of ICU patients. 16 Several factors could explain these results. First, pneumonia may be a localized infection, within which procalcitonin can be synthesized locally without systemic release (as in other such compartmentalized infections), thereby explaining its low serum level or apparent decline in patients with true pulmonary infections.…”
Section: See the Original Study On Page 412mentioning
confidence: 98%
“…Furthermore, modified CPIS lacks sensitivity (Ͻ80%), as described in the present and previous studies focusing on the simplified version of the CPIS. 13,[16][17][18] The relative neutrophil cell count (%) at various cutoff levels did not substantially improve the diagnostic performance of either modified CPIS or Johanson criteria. This result could be partially justified by the absence of a significant difference in neutrophil cell count between subjects with VAP and subjects with another diagnosis.…”
Section: Discussionmentioning
confidence: 99%